Mineral Resource Trade in Chile Contribution to Development and Policy Implications - Korinek, Jane (OECD Trade Policy Papers, 2013)
Mineral resources present a formidable source of wealth but a formidable challenge to regulate in order to maximize social welfare from their extraction. Some resource-rich countries, such as Chile, have been successful in developing their economies and managing their revenue streams effectively. Strong institutions and regulatory oversight have helped to capitalize on the benefits of the mining sector for economy-wide growth and development in Chile. This paper identifies some of the good practice areas in mining regulation in Chile whose economy has shown strong growth over most of the last two decades. Some of the areas touched on in this paper are the taxation of the minerals sector, management of the tax revenue, and policies designed to foster spillovers into other sectors of the economy and make the most of Chile's comparative advantage as a long-time global leader in the copper industry. The paper concludes that there is much to be learned from the Chilean experience in regulating its mining sector and many areas where it could be well used as a model for other mineral rich economies wishing to develop their mining sectors to enhance economy-wide growth